Participation in Field Learning and Teaching Opportunities: Avenues to Research and Publication. Issue 4 (3rd July 2016) - Albert, Donald; Strait, John; Fujimoto-Strait, Ava
ABSTRACT: Field experiences continue to be a hallmark of a geographer's education and, for that matter, reeducation, as we all strive to remain current in the real world. Academic geographers beginning their ascent towards tenure and promotion might consider augmenting their portfolios with materials emerging from field teaching and learning activities.